Prevalence, Clinical Characteristics, and Treatment Response in Patients with Post Cricoid Inlet Patch—A Descriptive Retrospective Study - Irshad H. Ali; Abhijith Bale; Umesh Jalihal; Praveen Kumar A. C.; Ajay Bale; Meghana Sreenath (Journal of Digestive Endoscopy, 2022)
Objectives The aim of this study was to determine the incidence of post cricoid inlet patch (PC-IP) and to assess the clinical characteristics, pathological features, and treatment response. Materials and Methods A retrospective cross-sectional study was conducted from April 2016 to April 2021 in the tertiary gastroenterology unit of urban India. All patients with symptoms of globus sensation, chronic cough, heartburn, hoarseness, throat pain, dysphagia, and acid regurgitation after a thorough clinical examination underwent esophagogastroduodenoscopy by experienced endoscopists including biopsy. Sociodemographic data, symptoms and its duration, previous hospital visits, and chronic proton pump inhibitor (PPI) use were noted during the study. Results  Three-thousand two-hundred fifty upper gastrointestinal endoscopies were performed during the study period. The prevalence of PC-IP was 2.7%, comprising 36.3% males and rest females. Mean age was 36.2 ± 17years. The most common symptom among these patients was globus sensation (81.8%) followed by acid regurgitation (75%), dyspepsia (64.7%), dysphagia (48.8%), throat pain (29.54%), chronic cough (22.72%), hoarseness (22.72%), and others (6.81%). Mean diameter of PC-IP was 1.5 ± 0.5 cm, more than one patch was found in 23.76% of patients. Histopathological examination showed heterotrophic gastric mucosa in 77.27%, out of which 38.23% had oxyntic type, 44.11% had mucoid type, and the rest had mixed cell type. On median follow-up after 20 months, 68.18% of patient had persistent symptoms, 77.27% were PPI responsive, and 22.73% were PPI refractory. On follow-up, 38.63% of patients had a repeat endoscopic procedure and biopsy (20.45%); none showed any changes in size or dysplasia. Conclusion Prevalence of PC-IP could be higher than the estimated. Careful examination of upper esophagus and use of narrow band imaging will increase the possibility of identifying IP. Those symptomatic patients need treatment with PPI, sometimes for long term. Ablative therapy with radiofrequency or argon plasma coagulation needs further clarification.